Slow crack growth behavior in Si3N4 sintered with Yb2Si2O7 tie-line composition additives - Choi, HJ; Kim, HJ; Lee, JG; Kim, YW (ELSEVIER SCI LTD, 2001)
Slow crack growth behavior of two gas pressure sintered Si3N4 ceramics with different additives; a Yb2Si2O7 composition and an Al2O3-Y2O3 composition, was investigated by constant stress-rate ("dynamic fatigue") testing at 1400 degreesC. The slow crack growth parameter. n, was 14.7 and 6.3 for Si3N4 With Yb2Si2O7 and Al2O3-Y2O3 compositions, respectively. Superior crack growth resistance of Si3N4 with Yb2Si2O7 composition was due to its higher refractoriness of intergranular glassy films, compared to Si3N4 with Al2O3-Y2O3 composition. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: SILICON-NITRIDE CERAMICS; OXIDATION BEHAVIOR; STRENGTH; SYSTEM; FILMS